Partisipasi Peserta Didik dalam Pelaksanaan Kegiatan Rumah Kompos untuk Mendukung Program Adiwiyata di SMP Negeri 2 Banjarnegara - Mulyadi, Wiwid Bangun; Setyowati, Dewi Liesnoor; Suroso, Suroso (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2019)
The implementation house of compost activities is used to support the adiwiyata program based on four components of the environment, namely environmentally sound policies, environment-based curricula, participatory based environmental activities, and environmentally friendly supporting compost houses. The aim of the research is to find out about the participation of students in the implementation of compost house activities to support the Adiwiyata's program in Junior High School 2 in Banjarnegara. The research used was a descriptive research method. The results showed that the implementation of compost houses in Banjarnegara Junior High School 2 was divided into three activities, it was planning, production, and marketing processes. Student participation in each of these activities: 1) participation in planning activities is categorized as low, students do not carry out careful planning 2) participation in production process activities is classified as moderate, because students have implemented but not according to procedure 3) participation in marketing activities is low, students carry out promotions in and outside of school, but in distribution activities only carried out in schools. Pelaksanaan kegiatan rumah kompos digunakan untuk mendukung program adiwiyata berdasarkan 4 komponen adiwiyata yaitu kebijakan berwawasan lingkungan, kurikulum berbasis lingkungan, kegiatan lingkungan berbasis partisipatif, dan sarana rumah kompos pendukung ramah lingkungan. Tujuan penelitian adalah mengetahui pelaksanaan kegiatan rumah kompos dalam mendukung program adiwiyata dan mengetahui partisipasi peserta didik dalam pelaksanaan kegiatan rumah kompos. Metode penelitian yang digunakan berupa metode penelitian deskriptif. Hasil penelitian menunjukkan bahwa Partisipasi peserta didik dilihat pada setiap kegiatan tersebut: 1) partisipasi dalam kegiatan perencanaan dikategorikan rendah, peserta didik tidak melaksanakan perencanaan dengan seksama 2) partisipasi dalam kegiatan proses produksi tergolong sedang, sebab peserta didik sudah melaksanakan namun tidak sesuai prosedur 3) partisipasi dalam kegiatan pemasaran tergolong rendah, peserta didik melaksanakan promosi didalam dan di luar sekolah, namun dalam kegiatan pendistribusian hanya dilaksanakan didalam sekolah.